Impulsive Shopping Behavior via Live Streaming on Shopee: Testing the Theory of Planned Behavior (A Study of Maranatha University Students) - Zefa Arya Nugraha; Anny Nurbasari (The Journal of Management, Digital Business, and Entrepreneurship, 2026)
This study aims to analyze impulsive buying behavior through live streaming on the Shopee e-commerce platform using the Theory of Planned Behavior as the theoretical framework. The method used in this study is a survey of Maranatha University students as respondents, aimed at exploring their perceptions of how various elements in live streaming influence impulsive buying behavior. The data were analyzed using Structural Equation Modeling (SEM) techniques and SmartPLS 3.0 software to test the relationships between the variables. The results of the hypothesis testing show that consumers’ attitudes toward impulsive buying are positively related to their intention to make impulsive purchases; subjective norms from their surrounding environment also have a positive effect on impulsive buying intention; and individuals’ perceptions of behavioral control also positively influence impulsive buying intention. Furthermore, impulsive buying intention significantly affects actual impulsive buying behavior on the Shopee live streaming platform. The author suggests that e-commerce platforms encourage the use of engaging marketing stimuli for consumers.